Pengaruh Rekrutmen, Pelatihan Kerja dan Rotasi Kerja terhadap Kinerja Pengawas dengan Revitalisasi sebagai Variabel Intervening pada APIP Level 3 di Sumatera Selatan - Desi Pitriani; Zunaidah Zunaidah; Isni Andriana (Universitas Batanghari Jambi, 2023)
The success of organizational activities is always associated with the evaluation results of the implementation of these activities. Supervision is needed as an evaluation in ensuring organizational activities run effectively and efficiently. Regional government supervision carried out by APIP level 3 in South Sumatra is carried out to prevent irregularities and abuse of authority. Supervision activities by APIP require sufficient supervisory resources, have the ability and skills in supervision, for this reason APIP carries out recruitment, job training and job rotation. these three things have an impact on the revitalization and performance of supervisors. This study aims to analyze the effect of recruitment, job training and job rotation on the performance of supervisors with revitalization as an intervening variable. Research using empirical survey with quantitative methods. 118 data samples from 6 inspectorates with APIP level 3 predicate in South Sumatra were collected and further analyzed using the Structural Equalition Model (SEM) based on goal setting theory. Recruitment factors, job rotation job training and revitalization as intervening factors were hypothesized and validated for direct and indirect significant effects on supervisory performance. The results of this study indicate that recruitment and job training directly and indirectly affect supervisor revitalization and performance. While recruitment has a direct effect on the performance of supervisors, then revitalization has succeeded in becoming an intervening element in job training and job rotation but not on recruitment. These findings contribute to knowledge, especially the practice of determination theory, where success in improving supervisory performance as an organizational goal can use recruitment, job training and job rotation. and use the revitalization process to become the mediator. Prospectively, the results of this study will provide informative insights for supervisors and APIP managers in carrying out recruitment, job training and job rotation in the process of improving supervisor performance.